Importance Of Improving Information Services In The Educational Management Of Pedagogical Higher Education Institutions - Buriyev Kholiddin Ja'farovich (Genius Journals, 2025)
This article examines the issues of improving the system of information services in the process of educational management at pedagogical higher education institutions. The significance of information services in enhancing the quality of education, their role in optimizing management through the centralized storage of regulatory documents related to the educational process, as well as data on students, has been analyzed. Furthermore, the role of interactive technologies, electronic learning platforms, and modern management mechanisms in the effective organization of the educational process is scientifically substantiated. The study justifies the necessity of adapting advanced foreign experiences to the national education system and highlights the sociopedagogical importance of information services in expanding the spiritual and professional potential of the pedagogical community.
Keywords: educational management; information service system; e-learning